Peran Pendidikan Islam dalam Mengembangkan Akhlak Generasi Muda - Vina Rayda Najiha; jasiah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
Social and digital change has reshaped the behavior of young people, making moral development through Islamic education an important need in family, school, and community life. This study is necessary because discussions of Islamic education remain normative, while the connection between moral formation, digital challenges, and youth development strategies is not yet explained concretely. The first research question asks how Islamic education contributes to developing the morals of young people, and the objective is to analyze its function in cultivating faith, worship, social ethics, and moral responsibility. The data were processed through library research by examining Qur’anic verses, books, and Indonesian scholarly journals published from 2020 to 2025, then analyzed using a descriptive-qualitative approach. The findings show that Islamic education contributes through six main aspects: exemplary conduct, worship habituation, advice, supervision, religious school culture, and Islamic digital literacy. This study concludes that Islamic education can form religious, polite, disciplined, caring, and wise young people who respond responsibly to changing times.